Measurement of Qualitative and Quantitative Variables in Economics (Surkhet Journal, 2025)
A comprehensive grasp of economics requires both qualitative and quantitative factors. Qualitative factors give depth and context, whereas quantitative variables enable exact, numerical analysis. Economists may create realistic models, arrive at precise findings, and make well-informed judgments by accurately measuring and integrating both kinds of data. Economists can now measure and evaluate a wide range of economic indicators more easily than ever before because to developments in econometrics and data analytics. The paper's goal is to create a measuring tool that will accurately assess the qualitative random variables. Respondents are provided with 180 possible responses using the Sama Radial Indicator (SRI), and the results are treated as a continuous random variable. As a result, it may be inferred that either the sampling distribution or the probability distribution of it will be roughly regularly distributed.